Evaluating the Financial Stability of Banking System, Considering the Emergence Property - Lesik Vitaliy O. (Bìznes Inform, 2017)
The article is concerned with analyzing the existing approaches to evaluation of the financial stability of banking system, substantiating the expedience of accounting, and generalizing the characteristics of the emergence property to determine its level. The article considers the interrelation of concepts of «financial stability» and «financial sustainability», the necessity of their correlation, taking account of the time factor, has been substantiated. A critical analysis of the approaches to evaluating the financial stability of banking system has been carried out, their eligibility according to the criteria of accounting of the identification attributes of systemacity and the analytical data aggregation has been examined. To determine the status of banking system as a system phenomenon, the necessity of carrying out an evaluation of its financial stability on the basis of the emergence approach has been substantiated, including the following directions: intensity of credit and financial interaction in the interbank market; functional load of the banking system as to ensuring the macroeconomic development; structural changes and financial disparities in the banking system; scale effects that arise as a consequence of change in the main financial parameters of the system banks.